A user guide to Ghana Africa research in sustainable intensification for the next generation (Africa RISING) baseline evaluation survey data - Azzarri, Carlo; Haile, Beliyou; Tinonin, Cecilia; Pan African Field Services Limited; Signorelli, Sara; Roberts, Cleophelia (International Food Policy Research Institute, 2016)
The Ghana Africa Research in Sustainable Intensification for the Next Generation (Africa RISING) Baseline Evaluation Survey (GARBES) survey was implemented from May to July 2014 as part of IFPRI’s Monitoring and Evaluation (M&E) of Africa RISING. Africa RISING aims to create opportunities for smallholder farmers in Africa south of the Sahara (through action research and development partnerships) by sustainably intensifying their farming systems and improving food, nutrition, and income security. Initiated in 2012, the program is supported by the United States Agency for International Development (USAID) as part of the U.S. government’s Feed the Future (FTF) initiative. The International Institute of Tropical Agriculture (IITA) leads a sustainable intensification effort focusing on the cereal-based farming systems in the Guinea Savannah Zone of West Africa (Ghana and Mali) and East and Southern Africa (Malawi, Tanzania, and Zambia) while the International Livestock Research Institute (ILRI) leads the research activities focusing on the crop-livestock systems of the Ethiopian highlands. The International Food Policy Research Institute (IFPRI) has been tasked with M&E of the three projects. Ghana Africa RISING is being implemented in Northern, Upper East, and Upper West regions of Ghana, within the FTF Zones of Influence. The research activities are led by IITA and Wageningen University (WUR). GARBES collected detailed household- and plot-crop level data addressing various topics: employment (agricultural and non-agricultural); health; agricultural land; crop inputs, harvest, storage, and sale; livestock ownership, feed, and water; agriculture-related challenges and coping strategies; credit and off-farm income sources; housing condition and ownership of various durable assets; subjective welfare and food security; household-level food consumption; non-food expenditure; agricultural shocks; and child and women anthropometry. The community survey collected data on access to basic services; extension services; social organizations, mobility, and village-level shocks; access to natural resources; metric conversion units; and prices of crops and food items. GARBES covered 1,284 households and 50 communities drawn from the three project regions. Data were collected using structured questionnaires in multiple local languages through Computer Assisted Personal Interviewing (using SurveyCTO).